2015
DOI: 10.1016/j.agrformet.2015.08.247
|View full text |Cite
|
Sign up to set email alerts
|

Understory CO2, sensible heat, and latent heat fluxes in a black spruce forest in interior Alaska

Abstract: An open black spruce forest, the most common ecosystem in interior Alaska, is characterized by patchy canopy gaps where the forest understory is exposed. This study measured CO2, sensible heat, and latent heat fluxes with eddy covariance (EC) in one of those large canopy gaps, and estimated understory fluxes in a black spruce forest in 2011-2014. Then understory fluxes and ecosystem fluxes were compared. The understory fluxes during the snow-free seasons were determined by two approaches. The first approach de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 58 publications
2
40
2
Order By: Relevance
“…When explaining seasonal variability in T birch / ET eco , we found that T birch / ET eco strongly depended on VPD and PAR, with T birch / ET eco saturating at high VPD, but this environmental control on T birch / ET eco was stronger in Abisko. Therefore, our results show an increased relative role of mountain birch in controlling ecosystem evapotranspiration as evaporative demand increases, especially in denser forests, in contrast with studies on waterlogged peatlands where understorey contribution increases with VPD (Ikawa et al, ). In our sites, mountain birch roots possibly access soil moisture at greater depths (Hunziker, Sigurdsson, Halldorsson, Schwanghart, & Kuhn, ), supplying water to meet the increasing evaporative demand and causing the increase in T birch / ET eco .…”
Section: Discussioncontrasting
confidence: 85%
“…When explaining seasonal variability in T birch / ET eco , we found that T birch / ET eco strongly depended on VPD and PAR, with T birch / ET eco saturating at high VPD, but this environmental control on T birch / ET eco was stronger in Abisko. Therefore, our results show an increased relative role of mountain birch in controlling ecosystem evapotranspiration as evaporative demand increases, especially in denser forests, in contrast with studies on waterlogged peatlands where understorey contribution increases with VPD (Ikawa et al, ). In our sites, mountain birch roots possibly access soil moisture at greater depths (Hunziker, Sigurdsson, Halldorsson, Schwanghart, & Kuhn, ), supplying water to meet the increasing evaporative demand and causing the increase in T birch / ET eco .…”
Section: Discussioncontrasting
confidence: 85%
“…By doing so, we were able to get an understanding of the in‐canopy to above‐canopy interactions occurring in the ambient and FACE setup. Footprint analysis showed that nearly all of our measurements originate within 5 m from the IRGASON device (Figure S5; Matthes et al, , Ikawa et al, ). Cospectral analysis revealed minimal flux loss at higher frequencies.…”
Section: Methodsmentioning
confidence: 87%
“…The points represent the measurement heights for air temperature, relatively humidity, CO 2 concentration and photosynthetic active radiation. Ikawa et al, 2015). Cospectral analysis revealed minimal flux loss at higher frequencies.…”
Section: Microclimate Measurementsmentioning
confidence: 92%
“…The rice paddy water was drained in late August and no further irrigation was applied until harvesting. Nonetheless, no relation was found between the ET / E P values and the normalized soil moisture data calculated following Ikawa et al 2015 . The variation in the timing of the water drainage was also not enough to explain the variation of the ET / E P values because 2009 exhibited higher ET / E P values than expected given the precipitation measurements, even though the water drainage started early August 12 .…”
Section: -2009mentioning
confidence: 97%